2020
DOI: 10.1039/d0dt01415j
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared cyclometalated iridium(iii) complexes with bipolar features for efficient OLEDs via solution-processing

Abstract: Double gain, a bipolar feature NIR iridium(iii) complex with both hole and electron transporting group to improve the OLED performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Yu and Zhu et al. reported a series of complexes with triazole rings condensed at the benzene ring of the C part of piq ( Yu et al., 2016 , 2019 , 2020 ), such as complex 30. Generally, the triazole is an isoelectronic species with the thiadiazole ring.…”
Section: Molecular Designs For Nir-emitting Ir(iii) Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…Yu and Zhu et al. reported a series of complexes with triazole rings condensed at the benzene ring of the C part of piq ( Yu et al., 2016 , 2019 , 2020 ), such as complex 30. Generally, the triazole is an isoelectronic species with the thiadiazole ring.…”
Section: Molecular Designs For Nir-emitting Ir(iii) Complexesmentioning
confidence: 99%
“…In addition to improving solubility, the side effect of flexible chains with the nonradiative loss is also suppressed. Moreover, the TPA group was frequently used to improve the hole transporting ability of complexes and their performances in OLED devices ( Yu et al., 2016 , 2019 , 2020 ).
Figure 8 Representative NIR-emitting Ir(III) complexes with aromatic substitutions and aromatic substitutions combined with flexible chains
…”
Section: Molecular Designs For Nir-emitting Ir(iii) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although NIR luminescent materials of pure organic molecules can simultaneously harvest both singlet and triplet excitons and the internal quantum efficiency can theoretically reach 100%, transition metal complexes are still been favored by researchers due to their good device stability and easy adjustment of emission wavelength. [2][3][4][5][6] Heretofore, cyclometalated platinum complexes are a class of NIR electrophosphorescent materials that have been studied earlier, with the highest efficiency and great development potential. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] For example, in 2016, Chi's group reported a series of 2-pyrazinyl pyrazolate platinum(II) complexes and found that the maximum emission peak is at 740 nm, the photoluminescence efficiency (F PLQY ) is as high as 81% and the undoped OLEDs based on the complex [Pt(fprpz) 2 ] achieve a maximum external quantum efficiency (EQE max ) of 24%.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that the metalated ligand should contain at least one common donor atom (N, P, O, S) and one carbon donor atom. 3 The carbon donor atoms usually involve alkyl, 4 aryl, 5 or benzyl. 4,6 In comparison with aryl carbons, the metalation of alkenyl carbons is much less common.…”
Section: Introductionmentioning
confidence: 99%